Manfaat Citicoline pada Tata Laksana Stroke Iskemik - Endy Juli Anto; Jekson Martiar Siahaan; Putri Chairani Eyanoer (PT Kalbe Farma Tbk., 2024)
Background: Stroke is the third most common disease after heart disease and cancer and the main cause of disability worldwide. The most common type of stroke, which accounts for around 85%-87% of cases, is ischemic stroke (IS). This report is to examine the benefits of citicoline for IS patients. Case: A 63-year-old male was admitted with a diagnosis of IS and electrolyte disturbances. General treatment is semi-Fowler’s position, oxygen, and maintaining fluid and nutritional intake. Specific management is RL infusion 20 gtt/minute, candesartan 1x16 mg, clopidogrel 1x75 mg, omeprazole 40 mg/24 h intravenous (IV), and citicoline 500 mg/12 h IV. The patient showed clinical improvement. Method: Articles in PubMed, Cochrane, and Google Scholar in February-April 2022 were searched to find relevant studies to be evaluated with inclusion and exclusion criteria. The full text was obtained and critically reviewed with the evidence-based medicine guidelines. The results are limited to systematic reviews and meta-analyses. Results: Five studies were deemed valid, important, and applicable. However, the quality of these studies varies. Conclusion: All studies show that citicoline use could potentially improve clinical outcomes in IS patients.